RELATIONSHIP BETWEEN NUTRITION INTAKE AND THE FITNESS OF MANUFACTURING WORKERS IN INDONESIA - Muhammad Ilyas; Dewi Sumaryani Soemarko; Nuri Purwito Adi; Dewi Yunia Fitria; Marsen Isbayu Putra; Yessi Kualasari (The Indonesian Journal of Public Health, 2021)
ABSTRACKIndonesia ranks fourth in the world out of 15 countries whose manufacturing industries contribute more than 10% to the Gross Domestic Product (GDP). Nowadays, one of the consequences of the rapid development of the manufacturing industry in Indonesia is related to work productivity. Each person's work productivity is not the same, one of them depends on the availability of nutrients in the body. Lack of nutritional consumption for someone from standard needs will affect health conditions, activities, and work productivity. Nutritional substances in workers also affect fitness in addition to other factors such as age, health status, nutritional status, nutritional status, gender, and psychological conditions. Based on the description above, it is necessary to study the relationship between nutritional status and physical fitness of workers in manufacturing companies in Indonesia. The study was cross sectional on 120 workers from 6 manufacturing companies in Indonesia which was conducted using cluster sampling. Assessment of individual characteristics was conducted by direct interview. Assessment of nutritional intake uses the Food Frequency Questionnaire (FFQ) and the results were categorized as appropriate and inappropriate based on the 2019 nutritional adequacy figure for the Indonesian population. The fitness assessment (physical capacity) used a six-minute walking test by an occupational specialist and was converted to Meters and categorized with a cut off of 4.5 Mets to be sufficient or insufficient. About one third of manufacturing workers were centrally obese. Characteristics The dietary intake according to the recommendation were only about 10%, namely the appropriate carbohydrate intake 11.7% (Frequency 8.46 times (533.22 gr)), suitable fat 12.5% (Frequency 2.75 times (57.14 gr)), and suitable protein 10% (Frequency 6.55 times (101.77 gr)). The physical capacity of manufacturing workers in Indonesia was categorized as sufficient as much as 75.8% of their workload. Factors that affect physical capacity, namely age ≥ 40 years have 4.37 times less physical capacity and protein intake affected physical capacity / fitness for workers (p = 0.02). About a third of manufacturing workers were centrally obese. The characteristic of food intake in accordance with the recommended nutritional adequacy of the Indonesian population was only about 10%. The physical capacity of manufacturing workers in Indonesia was categorized as sufficient as much as 75.8% of their workload. Factors that affected physical capacity were age and protein intake. Keywords: Food Intake, Food Frequency Questionnaire (FFQ), Manufacturing Worker, Fitness, Six-Minute Walking Test.